KESENJANGAN KUALITAS PELAYANAN DAN KEPUASAN NASABAH PERBANKAN - Rachmad Hidayat (Prodi Teknik Industri Universitas Muhammadiyah Gresik, 2018)
The purpose of the present research was to analyze conformity of service elements’ importance accordingto customers and bank’s performance. Sample taken was 100 customers of East Javanese banks by usingaccidental sampling technique. The employed analysis was one of importance and customers’ performance/ satisfaction. The analysis utilized Cartesian chart with four quadrants. Results indicated several aspects closely related to customers’ level of satisfaction, among them being tellers’ attention to customers, employees’ seriousness to serving customers, waiting time in queue, availability of ATM, and interest rate offered by the bank.